Factor analysis for soil test data: a methodological approach in environment friendly soil fertility management - Dahal, Hari (Journal of Agriculture and Environment, 2007)
Soil test data were used in factor analysis employing the Principal Component Analysis technique for the reduction and summarization of soil variables. Principal component analysis was found to be highly suggestive in analyzing soil test data on which a rational fertilizer nutrients recommendation can be made for a sustainable soil fertility management reign. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 8-19